The Effects of a Passing Longwall Face on the Roadway, Pillars, and Standing Supports in Northern West Virginia - David Gearhart; Gabriel Esterhuizen; Peter Zhang (International Conference on Ground Control in Mining, 2018)
"Researchers from the National Institute for Safety and Health (NIOSH) installed instruments in the track entry and in the pillars of a northern West Virginia longwall coal mine between two planned panels for the purpose of monitoring the behavior of the ground. The instruments included four cable bolt load cells to measure the change in gateroad loading, six borehole pressure cells to measure the loading in the pillars, three six-channel roof extensometers to measure roof sag, four convergence measurements on the cribs to measure the crib loading, and a multipoint borehole extensometer to measure the pillar expansion. The instrumentation was all connected through two multiplexers to a single Campbell Scientific permissible datalogger located about 350 feet outby the instruments. The goal of the project was to record all of the measurements as both longwall faces passed the site of the instrumentation and to use the data to calibrate numerical models.This report describes the recording of all of the measurements taken as the first panel approached and then passed the instrumentation site. This study provided valuable data related to the ground response and support performance that will be used to improve safety in longwall gateroads.INTRODUCTIONA longwall mine in northern West Virginia was selected as a second study site for an ongoing research project into gateroad layout and support design. The area was affected by a transition from limestone to sandstone in the roof. The entries were 16 feet wide, and the height was approximately 80 inches. The layout for the longwall panels was 1,170 feet wide by 4,000 feet long. The panel configuration was right-handed, and a three-entry gateroad was used between panels. The pillars next to the headgate were 137.5 feet by 115 feet center-to-center, and the pillars next to the tailgate were 275 feet by 100 feet center-to-center, with the crosscuts at 60 degrees. The width of the gateroad was a total of 215 feet."